Cardio-vascular remodelling during sacubitril/valsartan therapy in patients with heart failure and reduced ejection fraction. (4th February 2022) - Monosilio, S; Filomena, D; Luongo, F; Neccia, M; Sannino, M; Birtolo, IL; Cimino, S; Tonti, G; Pedrizzetti, G; Benedetti, G; Fedele, F; Maestrini, V; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Sacubitril/valsartan (S/V) benefits in patients with heart failure and reduced ejection fraction (HFrEF) are partially related to cardiac reverse remodelling, in terms of volumes reduction and function improvement.  Effects on vascular remodeling are less investigated. Purpose: To evaluate cardiac and vascular remodelling in a cohort of patients with HFrEF after six months of therapy with S/V. Methods: 50 patients with HFrEF eligible to start a therapy with sacubitril/valsartan were enrolled. Clinical evaluation and standard and advanced echocardiography were performed at baseline and after six months of follow up (FU). Standard left ventricular dimension and function parameters, global longitudinal strain (GLS) were calculated. Non-invasive pressure-volume curves (P-V loop) estimation was assessed with an off-line dedicated software using ST-E derived time-resolved LV volumes and brachial pressure as input. The following hemodynamic parameters were calculated based on P-V loop curves: left ventricular elastance (Ees), arterial elastance (Ea) and ventricular-arterial coupling (VAC). Results: At six months F/U, a reduction of NYHA class in the vast majority of patients was detected (NYHA Class ≥ II, baseline vs F/U = 100% vs 50%; p< 0, 001). Systolic and diastolic blood pressure were lower, in comparison with baseline values (119 ± 16 vs 126  ± 11 mmHg; p = 0, 002 and 71 ±  8 vs 78 ±  8 mmHg; p = 0, 001, respectively). At echocardiographic evaluation, left ventricular end-diastolic and end-systolic volumes decreased (p< 0.001 and p< 0, 001, respectively) and ejection fraction and GLS significantly improved (p< 0.001 and p < 0.001, respectively). Moreover, a significant reduction of Ea and a significant improvement of Ees and VAC were observed (p = 0.008, p< 0, 001 and p< 0, 001, respectively). Conclusion: Therapy with S/V in HFrEF patients determines both cardiac and vascular remodelling reflecting the complex mechanisms behind clinical improvement.